Implementation of mudharabah contracts between ship owners and fishermen in sanrobone village, Takalar district - Fifi alfiana; Muhammad Najib Kasim; Agus Salim (www.amertainstitute.com, 2024)
This research aims to analyze how mudharabah contracts are implemented between ship owners and fishermen in Sanrobone Village, Takalar Regency. A mudharabah agreement is a way of cooperation in Islamic economics involving capital owners (shahibul mal) and business managers (mudharib), where profits are shared according to the agreement made. This study applies a qualitative approach using descriptive methods, where information is obtained through in depth interviews, observation and documentation. The results of the research state that in the practice of mudharabah contracts in Sanrobone Village, the ship owner provides capital in the form of a boat and fishing equipment, while the fishermen are in charge of carrying out fishing operations. However, there are several challenges that must be faced in implementing this contract, such as a lack of understanding of sharia principles, distribution of profits that is not in line with the original agreement, and the risk of losses that have not been resolved fairly. The conclusion of this research is the need to increase sharia financial literacy among fishing communities and ship owners to ensure that mudharabah contracts are carried out in accordance with sharia principles, as well as the important role of supporting institutions in providing education and mediation.